The Syncopated Energy Algorithm for Rendering Real-Time Tactile Interactions - Tang, Fei; McMahan, Ryan P. (Frontiers in ICT, 2019)
In this paper, we present a novel vibrotactile rendering algorithm for producing real-time tactile interactions suitable for virtual reality applications. The algorithm uses an energy model to produce smooth tactile sensations by continuously recalculating the location of a phantom actuator that represents a virtual touch point. It also employs syncopations in its rendered amplitude to produce artificial perceptual anchors that make the rendered vibrotactile patterns more recognizable. We conducted two studies to compare this Syncopated Energy algorithm to a standard real-time Grid Region algorithm for rendering touch patterns at different vibration amplitudes and frequencies. We found that the Grid Region algorithm afforded better recognition, but that the Syncopated Energy algorithm was perceived to produce smoother patterns at higher amplitudes. Additionally, we found that higher amplitudes afforded better recognition while a moderate amplitude yielded more perceived continuity. We also found that a higher frequency resulted in better recognition for fine-grained tactile sensations and that frequency can affect perceived continuity.